Conversations with women in musical theatre leadership - Morgan, Amanda Wansa (Routledge, 2024)
"Most writers, composers, librettists and music directors who make their careers in musical theatre do so without specific training or clear pathways to progress through the industry. Women in Musical Theatre addresses that absence by drawing on the experiences of these women to show the many and varied routes to successful careers on, off and beyond Broadway. Conversations with Women in Musical Theatre Leadership features 15 interviews with Broadway-level musical theatre music directors, directors, writers, composers, lyricists, stage managers, orchestrators, music arrangers, designers, and other women in positions of leadership. Built around extensive interviews with women at the top of their careers in the creative and leadership spheres of musical theatre, these first-hand accounts offer insight into the jobs themselves, the skills that they require, and how those skills can be developed. Any students of musical theatre and stagecraft, no matter what level and in what setting from professional training to university and conservatory study, will find this an invaluable asset"--